Surgical Outcomes After Treatment of Urethral Complications Following Metoidioplasty in Transgender Men. Issue 2 (31st December 2021) - de Rooij, Freek P.W.; Falcone, Marco; Waterschoot, Mieke; Pizzuto, Giuseppe; Bouman, Mark-Bram; Gontero, Paolo; Lumen, Nicolaas; Pigot, Garry L.S.
ABSTRACT: Background: Several treatment options for urethral complications following metoidioplasty in transmen are described in the literature, yet little is known with regard to the surgical outcomes. Aim: The aim of this study was to analyze the surgical outcomes after treatment of urethral strictures and urethral fistulas following metoidioplasty. Methods: A multicenter retrospective cohort study was conducted with transmen treated for strictures and fistulas after metoidioplasty in 3 tertiary referral centers. Outcomes: The primary outcome was the recurrence-free rate after surgical treatment of urethral strictures and urethral fistulas over a time period of 3 years postoperatively. Results: Of 96 transmen included in this study with a urethral complication, 44 (46%) experienced a urethral fistula, 31 (32%) a urethral stricture, and 21 (22%) both complications simultaneously. The recurrence-free rate for urethral strictures following endoscopic management (ie, urethral dilation or direct visual internal urethrotomy) was 61% after 1, 50% after 2, and 43% after 3 years, compared to 82% following open treatment options after 1, 2, and 3 years ( P = .002). Open treatment options were Heineke-Mikulicz procedure (7/9, 78% success), excision and primary anastomosis (3/3, 100%), 2-stage without graft (9/9, 100%), pedicled flap urethroplasty (1/1, 100%), and buccal mucosa graft urethroplasty (2/4 [50%] single-stage, 1/1 [100%] 2-stage). The recurrence-free rate for small urethral fistulas located at the pendulous urethra was 79% after 1, and 72% after 2 and 3 years, compared to 45% after 1, and 41% after 2 and 3 years for large fistulas, generally located at the urethral anastomoses of the fixed urethra. Treatment options for urethral fistulas were fistulectomy (26/48, 54%), fistulectomy & (redo) colpectomy (7/11, 64%), buccal mucosa graft urethroplasty (1/1, 100%), and retubularization of the urethral plate (3/4, 75%). A colpectomy before or during reoperation of a urethral fistula at the proximal urethral anastomosis showed higher success rates compared to without a colpectomy (7/11 [64%] vs 2/13 [15%] respectively, P = .03). Clinical Implications: This study provides insight in the treatment possibilities and corresponding outcomes of urethral complications following metoidioplasty in transmen. Strengths & Limitations: Strengths were the relatively large sample size and the overview of multiple treatment options available. Limitations were the heterogeneity of the cohort, underexposure of some surgical modalities, and absence of patient-reported outcomes. Conclusion: Open surgical techniques show better long-term outcomes in the management of urethral strictures compared to endoscopic options, and a colpectomy is beneficial before or during urethral fistula repair at the proximal urethral anastomosis.